Design Method of High Speed Ratio Planetary Gear Transmission（NGWN（Ⅱ））Considering Efficiency and Dynamics Performance - Wang Jianxiang; Qin Datong (Jixie chuandong)
Aiming at the problem of the low efficiency of NGWN-type planetary gear transmission with high speed ratio,the low-loss gear design that is optimizing modification coefficients and addendum coefficients simultaneously,reducing the contact ratio to reduce the mesh power loss can be applied to improve the gear transmission efficiency obviously. However,the change of contact ratio has an effect on dynamics of gear transmission. The NGWN（Ⅱ） type planetary gear transmission is taken as the research object,firstly,the relation between the contact ratio and system efficiency is obtained. Then,the dynamics model of NGWN（Ⅱ） type planetary gear transmission is built,the relation between contact ratio and dynamics performance of low-loss gear design is obtained. In the end,the select range of the contact ratio by using low-loss gear design is given,a theoretical guidance for the design of high-ratio planetary gear transmission with high efficiency and good dynamics performance is provided.